Accuracy and Reproducibility Using Patient-Specific Instrumentation in Total Ankle Arthroplasty. (April 2017) - Daigre, Justin; Berlet, Gregory; Van Dyke, Bryan; Peterson, Kyle S.; Santrock, Robert
Background: Implant survivorship is dependent on accuracy of implantation and successful soft tissue balancing. System instrumentation for total ankle arthroplasty implantation has a key influence on surgeon accuracy and reproducibility. The purpose of this study was to determine the accuracy and reproducibility of implant position with patient-specific guides for total ankle arthroplasty across multiple surgeons at multiple facilities. Methods: This retrospective, multicenter study included 44 patients who received a total ankle implant (INBONE II Total Ankle System; Wright Medical Technology, Memphis, TN) using PROPHECY patient-specific guides from January 2012 to December 2014. Forty-four patients with an average age of 63.0 years underwent total ankle arthroplasty using this preoperative patient-specific system. Preoperative computed tomography (CT) scans were obtained to assess coronal plane deformity, assess mechanical and anatomic alignment, and build patient-specific guides that referenced bony anatomy. The mean preoperative coronal deformity was 4.6 ± 4.6 degrees (range, 14 degrees varus to 17 degrees valgus). The first postoperative weightbearing radiographs were used to measure coronal and sagittal alignment of the implant vs the anatomic axis of the tibia. Results: In 79.5% of patients, the postoperative implant position of the tibia corresponded to the preoperative plan of the tibia within 3 degrees of the intended target, within 4 degrees in 88.6% of patients, and within 5 degrees in 100% of patients. The tibial component coronal size was correctly predicted in 98% of cases, whereas the talar component was correctly predicted in 80% of cases. Conclusion: The use of patient-specific instrumentation for total ankle arthroplasty provided reliable alignment and reproducibility in the clinical situation similar to that shown in cadaveric testing. This study has shown that the preoperative patient-specific instrumentation provided for accuracy and reproducibility of ankle arthroplasty implantation in a cohort across multiple surgeons and facilities. Level of Evidence: Level III, retrospective comparative series.